2010
DOI: 10.2337/dc09-1941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Intensive Insulin Treatment During the Diabetes Control and Complications Trial (DCCT) on Peripheral Neuropathy in Type 1 Diabetes During the Epidemiology of Diabetes Interventions and Complications (EDIC) Study

Abstract: OBJECTIVETo evaluate the impact of former intensive versus conventional insulin treatment on neuropathy in Diabetes Control and Complications Trial (DCCT) intensive and conventional treatment subjects with type 1 diabetes 13–14 years after DCCT closeout, during which time the two groups had achieved similar A1C levels.RESEARCH DESIGN AND METHODSClinical and nerve conduction studies (NCSs) performed during the DCCT were repeated during the Epidemiology of Diabetes Interventions and Complications (EDIC) study by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
1
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 331 publications
(254 citation statements)
references
References 19 publications
9
230
1
14
Order By: Relevance
“…As the participants had had diabetes for an average of 18 years, it might be considered that this is an unusual and unrepresentative cohort; however, this is not the case. The Epidemiology of Diabetes Interventions and Complications (EDIC) study at 13-14 years after study closure (average diabetes duration of 26 years) found normal nerve conduction studies in 46% and 31% and clinical neuropathy in only 34% and 41% of intensively treated and conventionally treated patients, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…As the participants had had diabetes for an average of 18 years, it might be considered that this is an unusual and unrepresentative cohort; however, this is not the case. The Epidemiology of Diabetes Interventions and Complications (EDIC) study at 13-14 years after study closure (average diabetes duration of 26 years) found normal nerve conduction studies in 46% and 31% and clinical neuropathy in only 34% and 41% of intensively treated and conventionally treated patients, respectively [29].…”
Section: Discussionmentioning
confidence: 99%
“…In both diabetes types, the association of DSPN with diabetes duration is independent of patients' age [1,[11][12][13][14][15]. Although the exact prevalence of DSPN differs according to the diagnostic methodology used and the population selected (for example, hospitalbased vs. outpatient-based vs. community-based) [1], its association with diabetes duration remains significant [1,[11][12][13][14][15][16][17][18]. However, the following two important observations should not escape our notice:…”
Section: Duration Of Diabetesmentioning
confidence: 97%
“…Therefore, the effectiveness of strict glycemic control in reducing the incidence and progression of DSPN has been the object of several ambitious studies in both types of diabetes [16,19,20,[29][30][31][32][33]. However, an important difference has emerged between T1D and T2D.…”
Section: Hyperglycemiamentioning
confidence: 99%
“…The intensively treated patients who had a lower HbA 1c level during the 6.5-year study had significantly fewer events than the conventionally treated group during the 10-year posttrial period, despite similar HbA 1c levels in the 2 groups during the decade after the trial ended. 9 In contrast to UKPDS, 3 recent large randomized trials have shown no reduction in CV events with aggressive vs more conservative glucose control in patients with type 2 DM, possibly because of a longer mean duration of type 2 DM and a shorter duration of follow-up than in the UKPDS trial. 6,10,11 Indeed, after 3.5 years, the ACCORD (Action to Control Cardiovascular Risk in Diabetes) trial showed significantly higher all-cause mortality in type 2 DM patients randomized to intensive glycemic control as compared with conventional control; as a result, the glycemic control portion of ACCORD was stopped prematurely.…”
mentioning
confidence: 95%